النظام القانوني لاندماج الشركات التجارية - فوحمه, وفاء (جامعة الوادي.University eloued, 2022)
تهدف هذه الدراسة إلى عملية اندماج الشركات التجارية بصفة عامة على أنه عقد يضم بمقتضاه شركة أو أكثر إلى شركة أخرى، وذلك مع زوال الشخصية المعنوية للشركة المندمجة وتنتقل أصولها وخصومها إلى الشركة الدامجة، كما تبرز أهم صورها لظاهرة التركيز الاقتصادي في الحياة القانونية. وهذا من خلال المفهوم القانوني لعلمية الاندماج وبيان تمييزه عن الأنظمة المشابهة له وكيفية إجراءاته التي تبدأ من أصحاب فكرة الاندماج إلى إبرامه للعقد وصولا إلى الآثار القانونية التي تترتب عنها. هناك آثار منشئة للشركة بالنسبة للأطراف كالمساهمين وكذلك الدائنين والمدنين وآثار بالنسبة للعقود المبرمة التي تبرمها الشركات الداخلة في الاندماج.This study aims to clarify the process of merging commercial companies in general. It is a contract which merges one or more companies to another company. To do so, the merged comany's legal personality should be dismissed and it's assets and liabilities must be moved to the merging company. Moreover, this paper focuses on the main part of the economic concentration in the legal context through defining the merging process legally as well as distinguishing between other similar systems. It represents the procedures; starting with who suggests the idea moving to signing the contract as well as the rights and obligations arising from that contract. There are many rights and obligations concerning the stakeholders, debtors and creditors, and for the contrats signed by the companies merged.
م.س.ع.أ22
Keywords: اندماج الشركات، الشركة الدامجة أو الجديدة، الشركاء أو المساهمين، القانون التجاري الجزائري.; Merging companies, merging company, stakeholders, Algerian commercial law